Some psychological aspects in speech and hearing problems - Bhavani AD (Journal of All India Institute of Speech and Hearing, 1972)
Many Psychological factors are found to be associated with Speech andHearing Problems. They need a detailed study, so that the problems can beunderstood and therapeutic programmes can be outlined effectively. Many personswith such problems may not be able to come to the clinic. All the factors thatcontribute towards such problems are not known. Survey and screening programmeswould be helpful to discover some of these cases. One such screening was undertakenat Davanagere, when our staff camped there for three days